Reduction of a native fish fauna by alien species: an example from Brazilian freshwater tropical lakes - Latini, A. O.; Petrere, M. (Blackwell Publishing, 2004)
The consequences of introducing Cichla cf. monoculus Spix & Agassiz, Astronotus ocellatus (Agassiz) and Pygocentrus nattereri Kner into lakes in the River Doce basin, Brazil, on richness, diversity and efficiency of aquatic macrophytes as natural refugia to native fishes was investigated. Samples were taken from lakes with and without alien fishes in areas with and without aquatic macrophytes. The presence of alien fishes reduced richness and diversity of the native fish community. The refugia function, which could be attributed to the clustering of aquatic macrophytes, does not exist in these lakes probably because the alien fishes exploit such habitats for reproduction. Since introductions threaten the native fish diversity of the region, studies on regional dispersion and factors that minimise the spread of alien fishes are needed.
Keywords: alien species; Brazil; habitat heterogeneity; River Doce State Park; tropical fish community